The Legacy of Pre–Columbian Fire on the Pine–Oak Forests of Upland Guatemala - Harvey, William J.; Nogué, Sandra; Stansell, Nathan; Petrokofsky, Gillian; Steinman, Byron; Willis, Katherine J. (Frontiers in Forests and Global Change, 2019)
Mountain tropical forests of the Southern Maya Area (Pacific Chiapas and Guatemala, El Salvador and Northern Honduras) predominantly comprise pine and oak formations, which form intricate mosaics and complex successional interactions following large–scale fire. These forests have been transformed by the peoples of the Maya civilization through practices of horticulture, agriculture and architectural developments over thousands of years. Anthropogenic impacts and the extent of early human interaction with these upland forests is currently poorly understood. In this study we identify: (i) the natural baseline vegetation of the region; (ii) when human impact and agrarian practices began in the Maya uplands; and (iii) what impacts the Maya had on forest structure, composition, and successional regeneration. Past vegetation, anthropogenic use of fire, and faunal abundance were reconstructed using proxy analysis of fossil pollen, macroscopic charcoal, microscopic charcoal, and dung fungal spores (Sporormiella). Three phases of forest succession were identified from 4000B.C.E. to 1522CE that broadly overlap with the well–defined archaeological periods of (i) the Archaic (10,000–2000B.C.E.); (ii) Pre–Classic (2000B.C.E. –100C.E.); (iii) Terminal Pre–Classic (100–250C.E.); (iv) Classic (250–950C.E.); and (v) Post–Classic (950–1522C.E.). These results also include the earliest evidence for agriculture within the Southern Maya Area through presence of peppers (Capsicum) from 3850B.C.E. and the rise of maize cultivation (Zea mays) from 970B.C.E. Persistent high intensity burning driven by agricultural practices and lime production during the Late–Pre-Classic (400–100B.C.E.) to Classic Period resulted in a compositional change of forest structure c.150B.C.E. from oak (Quercus) dominated forests to pine (Pinus) dominated forests. The legacy of Pre–Columbian anthropogenically driven fire in these mountain tropical forests demonstrates the resilience and thresholds for fire driven succession. These findings are particularly relevant for addressing current land use and management strategies involving agriculture, fire, and forest management in the mountain tropical forests of the Southern Maya Area.